Cornual Ectopic Pregnancy: Case Series - Baral, G; Shakya, B; Silwal, J (Nepal Journal of Obstetrics and Gynaecology, 2015)
Three cases of cornual pregnancies encountered within three weeks at Paropakar Maternity and Women’s Hospital had diverse presentations. Fortunately, in all three case series, cornual resection was performed successfully. Cornual pregnancy is difficult to diagnose preoperatively with low ultrasonographic sensitivity and is easily confused with tubal ectopic pregnancy or a normal intrauterine pregnancy. Diagnosis before rupture is essential to prevent mortality and potential loss of fertility. The surgical management of diagnosed cornual pregnancy consists of hemostasis, resection, repair and reconstruction.